Response of microbial community of surface and deep chlorophyll maximum to nutrients and light in South China Sea - Gong, Fahui; Zhang, Yafeng; Xie, Wei; Wu, Xiuqin; Zhang, Han; Huang, Suixuan; Gong, Jun; Yin, Kedong (Frontiers in Marine Science, 2023)
In oligotrophic seas such as South China Sea, the subsurface or deep chlorophyll maximum (DCM) is always present. The surface planktonic community receives sufficient light, but is short of nutrients. The DCM layer is under light limitation, but frequent supply of nutrients. Therefore, vertical mixing becomes critical in determining their community composition and drives their changes by responding to light and nutrients. In this study, we conducted an onboard experiment by collecting seawater samples at surface and the DCM layer and adding nutrients, and incubated them under full sunlight and 10% light, and examined the diversity of bacterial and eukaryotic communities and their cell abundance using 16/18S high throughput sequencing and FCM approaches. Our study found large differences in bacterial and eukaryotic community structure and cell abundance between the surface and DCM. After 72 hours of culture, taxonomically the incubated surface water was dominated by pico-eukaryotic phytoplankton, while the incubated DCM layer water is dominated by diatoms, which suggests diatoms are the main functional group of phytoplankton bloom after a vertical mixing event. These findings indicate that phytoplankton at the DCM respond to enhanced light and frequent supplied nutrients due to vertical mixing and thus maintain primary productivity in the otherwise oligotrophic oceans.